Evaluation of alternative distribution network design strategies - Gan, Chin Kim (2009)
A statistical distribution network design tool has been developed to quantitatively assess the impact of alternative distribution network investment plans in terms of capital costs, losses and reliability. In contrast to idealistic and network specific design approaches, this paper presents a statistical assessment approach in which the optimal network design policies are determined by evaluating the costs and benefits of different designs applied on a number of networks with similar properties such as consumer distributions, types, numbers and load density. Simulations have been carried out on multiple voltage levels (LV, MV and HV).